2019
DOI: 10.1080/22221751.2018.1562849
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic diversity and clinical outcome of cryptococcosis in renal transplant recipients in Brazil

Abstract: Genotypic diversity and fluconazole susceptibility of 82 Cryptococcus neoformans and Cryptococcus gattii isolates from 60 renal transplant recipients in Brazil were characterized. Clinical characteristics of the patients and prognostic factors were analysed. Seventy-two (87.8%) isolates were C. neoformans and 10 (12.2%) were C. gattii . VNI was the most common molecular type (40 cases; 66.7%), followed by VNII (9 cases;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 58 publications
0
20
0
Order By: Relevance
“…The combined analysis of the molecular data also showed that only in Mexico have all eight major molecular types been reported, while in Brazil and Argentina, there are no reports of VGIV isolates, and in Colombia, VNIII has not been reported ( Figure 1 ). However, in Brazil, 13 VNB isolates, previously thought to be exclusive from Botswana, have been reported not only from the environment [ 75 ], but also from clinical cases [ 85 ]. Also in Brazil, a new singular cluster, denominated as AFLP1C, representing a unique molecular type, was identified in 23 isolates [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…The combined analysis of the molecular data also showed that only in Mexico have all eight major molecular types been reported, while in Brazil and Argentina, there are no reports of VGIV isolates, and in Colombia, VNIII has not been reported ( Figure 1 ). However, in Brazil, 13 VNB isolates, previously thought to be exclusive from Botswana, have been reported not only from the environment [ 75 ], but also from clinical cases [ 85 ]. Also in Brazil, a new singular cluster, denominated as AFLP1C, representing a unique molecular type, was identified in 23 isolates [ 77 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, in 62 Cryptococcus strains collected from meningitis cases from 2006 to 2010 in Brazil, C. gattii species complex accounted for 21%, tremendously higher than that in mainland China ( Matos et al, 2012 ). In addition, there are several studies in Brazil also showing a high prevalence of C. neoformans species complex ( Andrade-Silva et al, 2018 ; Ponzio et al, 2019 ). Infection due to C. gattii species complex is more prevalent in the Northeast of Brazil ( Matos et al, 2012 ), despite has been described in the Southeast ( Vilas-Boas et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…VNII is associated with higher laccase production compared to both VNI and VNB clinical isolates as well as increased survival in ex-vivo CSF [ 111 ]. In addition, among a small cohort of 60 renal transplant recipients, nine patients infected with VNII strains had high survival rate compared to patients infected with strains of other molecular types [ 113 ]. This observation identifies a need for more robust studies to understand and characterize the relationships between cryptococcal molecular types and outcomes in transplant recipients.…”
Section: Associations Between Cryptococcal Genotypes and Clinical Presentationmentioning
confidence: 99%
“…Within the C. gattii species complex, both VGI and VGII disproportionately infect HIV-negative/immunocompetent individuals while VGIII and VGIV lineages primarily infect immunocompromised and HIV-infected individuals [ 98 ]. VGII is associated with high mortality among renal transplant patients in Brazil [ 113 ]. VGIV is positively associated with giant cells which are common in PC infections, higher CD4 counts and negatively associated with lumbar puncture opening pressures (e.g., decreased intracranial pressures), nausea, and vomiting [ 98 ].…”
Section: Associations Between Cryptococcal Genotypes and Clinical Presentationmentioning
confidence: 99%